VISUALIZING PARABOLA: THE STUDY OF A MANIPULATIVE’S EFFECTIVENESS - Eyus Sudihartinih; Tia Purniati (LP4MK STKIP PGRI Lubuklinggau, 2019)
There are manipulatives to help students of mathematics education visualize parabola concepts. This article will show you how they have been used in analytic geometry classes, and provide the results of studies on their effectiveness. Participants are divided into two classes, the experimental class that lectures with manipulatives, and the control class without the use of manipulatives. The instruments used are a test, interview guide, and a questionnaire. The results of the data analysis show an improved understanding of student parabola concepts that use manipulatives better than students who do not use manipulatives. Based on the interviews show that students have good geometry abilities on the concept of the parabola by using manipulatives. The student's attitude toward learning with manipulatives is positive.